Sistema de injeção em fluxo espectrofotométrico para monitorar peróxido de hidrogênio em processo de fotodegradação por reação foto-Fenton - Oliveira, Mirela C. [UNESP]; Nogueira, Raquel Fernandes Pupo [UNESP]; Gomes Neto, José Anchieta [UNESP]; Jardim, Wilson F.; Rohwedder, Jarbas J. R. (Sociedade Brasileira de Química, 2001)
A flow injection spectrophotometric system was projected for monitoring hydrogen peroxide during photodegradation of organic contaminants in photo-Fenton processes (Fe2+/H2O2/UV). Sample is injected manually in a carrier stream and then receives by confluence a 0.1 mol L-1 NH4VO3 solution in 0.5 mol L-1 H2SO4 medium. The product formed shows absorption at 446 nm which is recorded as a peak with height proportional to H2O2 concentration. The performance of the proposed system was evaluated by monitoring the consumption of H2O2 during the photodegradation of dichloroacetic acid solution by foto-Fenton reaction.
Flow injection spectrophotometric system for hydrogen peroxide monitoring in photo-Fenton degradation processes
Keywords: hydrogen peroxide; flow injection analysis; foto-Fenton